ANALISIS SEMIOTIKA PUISI BAHASA MELAYU MANADO œCAP TIKUS BLUES KARYA FREDY WOWOR - Palit, Anatje Tineke; Humena, Stefanie; Pua, Christo Rilco; Karouw, Stella (BASASTRA: JURNAL KAJIAN BAHASA DAN SASTRA INDONESIA, 2023)
This research is a study of the science of sign or semiotic, which aims to reveal the cultural meaning of Manado-Malay speaking community. The sign discussed is the sign found in Manado-Malay poem entitled "Cap Tikus Blues" by Minahasa poet Fredy Wowor. This poem was chosen since it is considered relevant to the context of the time and various generations. As for this research is a qualitative research, thus, the method used is a descriptive qualitative method or a study that describes the object under study in accordance with the function and nature of the object. Poetry in this study is studied and described based on the nature of the object or reference as stated by Charles Sanders Pierce, namely (1) icons (2) indexes, and (3) symbols. The results of the research show that these three signs are found in the poem discussed above. Symbol is the most common sign type, followed by index, and icon consecutively. The cultural meaning or message contained therein is advice that seeks to remind and criticize one another regarding the positive and negative impacts of alcohol. In addition, the results of this study show that poetry is not only a medium for expressing poets' feelings, but also as a forum for disseminating ideas as well as social criticism for the wider community.